The implications of Qassem Soleimani assassination on US- Iranian relations - Abdallah, Noura Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
This study deals with the repercussions of the assassination of Iranian military commander Qassem Soleimani on US- Iranian relations, and the US- Iranian escalation and tension in Iraq and the entire surrounding region. The study tries to determine the indicators of the US- Iranian escalation and the effect of the bombing incident near Baghdad Airport on January 4, 2020, at the interior of Iranian, and at the regional and international level. It seeks to estimate the potential for escalation between the United States of America and Iran; the latter surprised the group of 4 + 1 countries on the anniversary of Soleimani assassination in 2021 by increasing the rate of uranium enrichment to 20%. This step will be taken in consideration in any future negotiations between Iran and the United States of America and the European Union if US President Joe Biden decides to return to the nuclear accord. The results of the study concluded that the previous US approach in the Trump administration affected negatively on any future negotiation about the return of US to the Joint Comprehensive Plan of Action. US President Joe Biden is trying to mitigate his predecessor’s escalation of US- Iranian relations; nonetheless, Israel seeks to obstruct any path that would end the tension between Washington and Tehran.